Expression and Preparation of a G‐Protein‐Coupled Cannabinoid Receptor CB2 for NMR Structural Studies. (9th January 2019) - Yeliseev, Alexei
Abstract: Cannabinoid receptor type II, or CB2, is an integral membrane protein that belongs to a large class of G‐protein‐coupled receptors (GPCR)s. CB2 is a part of the endocannabinoid system, which plays an important role in the regulation of immune response, inflammation, and pain. Information about the structure and function of CB2 is essential for the development of specific ligands targeting this receptor. We present here a methodology for recombinant expression of CB2 and its stable isotope labeling, purification, and reconstitution into liposomes, in preparation for its characterization by nuclear magnetic resonance (NMR). Correctly folded, functional CB2 labeled with [ 13 C, 15 N]tryptophan or uniformly labeled with 13 C and 15 N is expressed in a medium of defined composition, under controlled aeration, pH, and temperature conditions. The receptor is purified by affinity chromatography and reconstituted into lipid bilayers in the form of proteoliposomes suitable for analysis by NMR spectroscopy. © 2019 by John Wiley & Sons, Inc.